The influence of LLLT applied on applied on calvarial defect in rats under effect of cigarette smoke (Journal of Applied Oral Science, 2022)
Objective: Considering the global public health problem of smoking, which can negatively influence bone tissue repair, the aim of this study is to analyze the influence of photobiomodulation therapy (PBM) on calvaria defects created surgically in specimens under the effect of cigarette smoke and analyzed with use of histomorphometric and immunohistochemistry techniques. Methodology: Calvaria defects 4.1 mm in diameter were surgically created in the calvaria of 90-day-old rats (n=60) that were randomly divided into 4 experimental groups containing 15 animals each: control group (C), smoking group (S), laser group (L), and smoke associated with laser group (S+L). The animals were subjected to surgery for calvaria defects and underwent PBM, being evaluated at 21, 45, and 60 days post-surgery. The specimens were then processed for histomorphometric and immunohistochemistry analyses. The area of bone neoformation (ABN), percentage of bone neoformation (PBNF), and the remaining distance between the edges of the defects (D) were analyzed histometrically. Quantitative analysis of the TRAP immunolabeled cells was also performed. The data were subjected to analysis of variance (ANOVA) in conjunction with Tukey’s test to verify the statistical differences between groups (p<0.05). Results: The smoking group showed less ABN compared to the other experimental groups in all periods, and it also showed more D at 21 days compared to the remaining groups and at 45 days compared to the laser group. The smoking group showed a lower PNBF compared to the laser group in all experimental periods and compared to smoking combined with LLLT group at 21 days. Conclusions: PBM acted on bone biomodulation, thus stimulating new bone formation and compensating for the negative factor of smoking, which can be used as a supportive therapy during bone repair processes.